Modulation of Circulating Inflammatory Biomarkers by SGLT2 Inhibitors in Diabetic Patients with Acute Myocardial Infarction: A Quantitative Meta-Analysis of Laboratory Evidence: SGLT2 Inhibitors and Inflammatory Biomarkers in Diabetic AMI - Xu, Jia; Jie, Yuanhong; Dong, Tao; Li, Qi; Liu, Xiaobing (Journal of Medical Biochemistry, 2026)
Background: Acute myocardial infarction (AMI) in patients with type 2 diabetes mellitus (T2DM) is characterized by an exaggerated inflammatory response and adverse myocardial remodeling. Sodium–glucose cotransporter-2 inhibitors (SGLT2-I) have demonstrated cardiometabolic benefits; however, their effects on circulating inflammatory biomarkers in diabetic AMI remain inconsistent. This meta-analysis aimed to quantitatively evaluate laboratory-based evidence regarding the modulation of key inflammatory markers by SGLT2-I therapy in this high-risk population.Methods: A systematic search of PubMed, Embase, Cochrane Library, Web of Science, CNKI, and Wanfang databases was conducted up to December 2025. Randomized controlled trials and prospective cohort studies involving T2DM patients with AMI were included. Primary laboratory endpoints were circulating inflammatory biomarkers (interleukin-6 [IL-6], high-sensitivity C-reactive protein [hs-CRP], tumor necrosis factor-α [TNF-α]). Secondary outcomes included left ventricular ejection fraction (LVEF) and major adverse cardiovascular events (MACE). Data were pooled using fixed- or random-effects models according to heterogeneity. Evidence certainty was assessed using GRADE methodology.Results: Thirteen studies comprising 2,453 patients were included. SGLT2-I therapy was associated with significant reductions in IL-6 (MD = −2.33, 95% CI: −4.29 to −0.37; p < 0.001) and hs-CRP levels (MD = −1.90, 95% CI: −2.30 to −1.49; p < 0.001), indicating attenuation of systemic inflammatory activity. No statistically significant reduction was observed for TNF-α (MD = −2.66, 95% CI: −6.66 to 1.33; p = 0.19), potentially due to inter-study heterogeneity and limited sample size. Beyond biomarker modulation, SGLT2-I treatment was associated with improved LVEF and reduced MACE risk. Overall evidence quality was graded as moderate.Conclusions: This meta-analysis provides laboratory-based evidence that SGLT2 inhibitor therapy is associated with significant reductions in circulating IL-6 and hs-CRP levels in diabetic patients with AMI, supporting a potential anti-inflammatory mechanism beyond glucose lowering. These findings highlight the translational relevance of inflammatory biomarkers in evaluating cardiometabolic therapeutic strategies and underscore the need for larger mechanistic studies to further clarify biochemical pathways involved.
Keywords: SGLT2 inhibitors; inflammatory biomarkers; IL-6; hs-CRP; acute myocardial infarction; diabetes mellitus; meta-analysis